The church in fourteenth-century Iceland : the formaton of an elite clerical identity - Sigurdson, Erika (Northern world, 2016)
In The Church in Fourteenth-Century Iceland , Erika Sigurdson provides a history of the fourteenth-century Icelandic Church with a focus on the the social status of elite clerics following the introduction of benefices to Iceland. In this period, the elite clergy developed a shared identity based in part on universal clerical values, but also on a shared sense of interdependence, personal networks and connections within the framework of the Church. The Church in Fourteenth-Century Iceland examines the development of this social group through an analysis of bishops' sagas, annals, and documents. In the process, it chronicles major developments in the Icelandic Church after the reforms of the late thirteenth century, including its emphasis on property and land ownership, and the growth of ecclesiastical bureaucracy.